Kualitas Pelayanan Terhadap Kepuasan Muzakki Pada Inisiatif Zakat Indonesia (IZI) Kalimantan Timur - Abdiannur, Abdiannur; Arifin, Nico (Jurnal GeoEkonomi, 2019)
This study aims to determine whether the variable quality of tangible service, reliability, responsiveness, assurance, empathy simultaneously or partially has an influence on Muzakki satisfaction on the Indonesian Zakat Initiative (IZI) of East Kalimantan. The sample in this study is muzakki who has made alms profession at the Indonesian Zakat Initiative (IZI) in East Kalimantan. The analytical tool used is multiple linear regression. The results showed that simultaneously service quality variables (tangible, reliability, responsiveness, assurance and empathy) had an significant effect on Muzakki’s satisfaction on the Indonesian Zakat Initiative (IZI) of East Kalimantan. Partially, the guarantee variable has a significant and dominant effect on Muzakki’s satisfaction on the Indonesian Zakat Initiative (IZI) of East Kalimantan.